Modeling airline MRO operations using a systems dynamics approach: A case study of Turkish Airlines - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2018)
Purpose The life span of an aircraft is usually around 30 years in the commercial aviation industry. During this time span, aircraft needs maintenance to stay in service. The cost of maintenance, repair and overhaul (MRO) activities in its pure nature is a significant portion of operations, accounting around 10 percent of all cost drivers. The purpose of this paper is to design/develop and critically assess a comprehensive model of operations at Turkish Technic - the MRO department of Turkish Airlines. Design/methodology/approach A comprehensive systems dynamics model is designed and developed to holistically represent and critically assess the different facets of MRO operations to help in analyzing various decision scenarios at Turkish Airlines. Findings The developed system dynamics (SD) model presented unique opportunities to test various MRO operations' work load and aircraft fleet expansion policy alternatives. The model can also be used as a learning laboratory by altering various system parameters and testing different policies. The case study results suggested that MRO operations have a direct impact on the available number of airworthy aircrafts and hence, the usable fleet seat capacity; to sustain a profitable airline fleet, the airline companies should take into account the unique characteristics/needs of MRO operations for both existing and new/prospective aircrafts. Originality/value There are several SD studies in the literature focusing on the airline industry, but the MRO operations are virtually neglected in them. Hence, the proposed SD model contributed to the extant literature. The value of the developed model stems from its potential use in the critical analysis of decision scenarios as well as being leveraged as a training/learning laboratory.
Keywords: Aviation industry; Sensitivity analysis; Systems dynamics; Aircraft readiness; Maintenance; repair and overhaul (MRO); SIMULATION-MODEL; TRANSPORTATION; MAINTENANCE